An Analysis Of The Lexical and Contextual Meaning Of The Poem "Still I Rise" By Maya Angelou - Siti Armelia Hamidah; Anggit Laesa Oktaviani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study looks at the meanings of words and their context in Maya Angelou’s poem "Still I Rise." This poem is well-known for its message of strength and empowerment, especially for African American women during the civil rights movement. Using a qualitative approach, this research combines examining the text and interpreting its context. The lexical analysis looks at dictionary definitions of important words in the poem and their deeper meanings within the poem’s context. The contextual interpretation places the poem within the larger historical and cultural background of Angelou's life and the civil rights era. The findings show that Angelou’s use of language not only strengthens the poem’s themes of defiance and self-worth but also deeply connects with the socio-political climate of its time. The study aims to provide a deeper understanding of the lexical and contextual meanings of some of the lines in Angelou's literary work "Still I Rise" as well as in discussions of race, identity and empowerment.